2015
DOI: 10.1371/journal.pgen.1005141
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Swap of Anopheles gambiae's Assortative Mating Preferences Demonstrates Key Role of X-Chromosome Divergence Island in Incipient Sympatric Speciation

Abstract: Although many theoretical models of sympatric speciation propose that genes responsible for assortative mating amongst incipient species should be associated with genomic regions protected from recombination, there are few data to support this theory. The malaria mosquito, Anopheles gambiae, is known for its sympatric cryptic species maintained by pre-mating reproductive isolation and its putative genomic islands of speciation, and is therefore an ideal model system for studying the genomic signature associate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
50
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(55 citation statements)
references
References 58 publications
5
50
0
Order By: Relevance
“…This could not only provide females with a mechanism for selecting high-quality males (Cator et al, 2010;Pennetier et al, 2010) but also play a role in the assortative mating of A. coluzzii and A. gambiae. Crucially, the hypothesis that assortative mating could be mediated by females is supported by the results of a recent study by Aboagye-Antwi et al (2015); behavioural assays in recombinant strains for the M and S markers in the X chromosome of both Anopheles species revealed that females, but not males, mated assortatively, indicating that a species recognition mechanism appears to be female dependent. This, however, does not mean that males do not contribute to assortative mating in nature; in the field, males are known to contribute to assortative mating via swarm spatial segregation (Diabaté et al, 2006;Dabiré et al, 2013;Sawadogo et al, 2013;Aboagye-Antwi et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…This could not only provide females with a mechanism for selecting high-quality males (Cator et al, 2010;Pennetier et al, 2010) but also play a role in the assortative mating of A. coluzzii and A. gambiae. Crucially, the hypothesis that assortative mating could be mediated by females is supported by the results of a recent study by Aboagye-Antwi et al (2015); behavioural assays in recombinant strains for the M and S markers in the X chromosome of both Anopheles species revealed that females, but not males, mated assortatively, indicating that a species recognition mechanism appears to be female dependent. This, however, does not mean that males do not contribute to assortative mating in nature; in the field, males are known to contribute to assortative mating via swarm spatial segregation (Diabaté et al, 2006;Dabiré et al, 2013;Sawadogo et al, 2013;Aboagye-Antwi et al, 2015).…”
Section: Discussionmentioning
confidence: 85%
“…; Aboagye‐Antwi et al . ; Twyford & Friedman ). However, critically lacking is an understanding of the relative contributions of ecological divergence and assortative mating to rearrangement spread in populations.…”
Section: Introductionmentioning
confidence: 99%
“…A new inversion can also be favoured if it contains both a locus which contributes to assortative mating and a locus which contributes to hybrid inviability (Trickett & Butlin 1994;Dagilis & Kirkpatrick 2016). Empirical data support the presence of loci within rearrangements that contribute to sexual and ecologically important traits (Day & Butlin 1987;Lowry & Willis 2010;Ayala et al 2012;Andrew & Rieseberg 2013;Friedman & Willis 2013;Oneal et al 2014;Aboagye-Antwi et al 2015;Twyford & Friedman 2015). However, critically lacking is an understanding of the relative contributions of ecological divergence and assortative mating to rearrangement spread in populations.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent analyses have shown that divergence is more widespread around the genome than first thought517 and the involvement of two of the three islands of divergence in early-stage speciation became controversial5181920. However, a recent laboratory study has demonstrated that the chromosome-X island of divergence is associated with assortative mating between A. coluzzii and A. gambiae 21 confirming this genomic region as a primary candidate location for genes involved in reproductive isolation. These species have also shown differences in at least two genes which contribute to medically important phenotypes.…”
mentioning
confidence: 99%